PENGEMBANGAN MODUL BERBASIS PBL TERINTEGRASI PISA MATERI BANGUN RUANG SISI LENGKUNG - Pratama, Nasya Aprina; Pasaribu, Feri Tiona; Gustiningsi, Tria; Nusantara, Duano Sapta (LPPM Universitas Bina Bangsa, 2025)
The purpose of this study was to develop and determine the quality of the product in the form of a PBL (Problem Based Learning) Integrated PISA (Programme For International Student Assessment) Module on the Curved Side Space Building material. This type of research is R&D (Research and Development) development research using the Four-D (Define, Design, Develop, Disseminate) development model. The subjects of the study were students of grades IX J and IX K of Secondary School Number 11 Kota Jambi. The research instruments used included validation questionnaire sheets, practicality questionnaire sheets. The product in the form of a PBL-based Module integrated with PISA was declared valid with a percentage of expert assessment of 88.1% in the